A price-based life cycle impact assessment method to quantify the reduced accessibility to mineral resources value - Ardente, Fulvio; Beylot, Antoine; Zampori, Luca (The international journal of life cycle assessment, 2023)
Purpose Several methods were developed to quantify the damage to mineral resources in LCA. Building on these and further expanding the concept of how to assess mineral resources in LCA, the authors developed in previous articles a method to account for dissipative resource flows in life cycle inventory (LCI). This article presents a price-based life cycle impact assessment method to quantify the potential impact of dissipative uses of resources. Methods This article firstly defines an impact pathway from resource use to resource dissipation and subsequent damage to the safeguard subject for “mineral resources”. It explores the quantification of this damage through the definition of characterization factors (CFs), for application to dissipative flows reported in LCI datasets. Market prices are used as a relevant proxy for the multiple, complex and varied functions and values held by mineral resources. Price data are collected considering a 50-year timeframe. Intervals of 10, 15, 20 and 30 years are considered for sensitivity analysis. Price-based CFs are tested on one cradle-to-gate case-study (copper production), in combination with accounted resources dissipated across the life-cycle. An approach to calculate the normalization factor (NF) is explored at the EU level. Results and discussion CFs are calculated for 66 mineral resources, considering copper as reference substance. Precious and specialty metals have the largest CFs. Minerals are instead ranked at the bottom of the hierarchy. New insights that this method brings in LCA are discussed for the copper production case-study. Losses due to final disposal of tailings are key (90% of total value loss), as opposed to e.g. emissions to environment. Relevance, robustness, completeness and consistency of the price-based CFs are discussed. This method in particular offers a relatively large coverage of elementary flows, with underlying data of good quality. Sensitivity of CFs to the chosen time interval is relatively limited. Initial analysis for a NF based on 14 key resources dissipated in the EU in 2016 is presented. Conclusions The developed CFs are relevant to address the issue of mineral resources value loss in LCA. They may be used in combination with dissipation-based methods at the LCI level, as tested in this study, or potentially (i) with classical extraction-based LCI datasets or (ii) as potential complements to existing life cycle impact assessment methods not capturing damage to resource value. Future refinements shall aim at extension to additional mineral resources and investigate the possibility of regionalisation of CFs and NF calculation.